Tradução e adaptação transcultural do instrumento "Pharmacists' Inventory of Learning Styles" (PILS) para aplicação na realidade brasileira - Cardoso, Geovanna Cunha (2015)
The identification of learning styles can be a vehicle to promote self-reflection between members of universities, teachers, tutors and students, necessary for the practice change. In this context, a study was conducted in order to translate and crossculturally adapt the instrument "Pharmacists' Inventory of Learning Styles" (PILS) for use in Brazilian pharmaceutical education. The process comprised five steps: (i) two independent translations, (ii) synthesis of translations, (iii) backtranslation, (iv) review by expert committee and (v) pilot study. Native translators in Portuguese and English languages conducted three first steps with liguistic rigor and solving up ambiguities or discrepancies by consensus among members and researcher. Expert committee analyzed semantic, idiomatic, conceptual and cultural equivalences between the original and the translated version. The average agreement for all stages of evaluators was 92.4% and ten items (58%) suffered some type of change. In pretest, 48 participants among pharmacy students (27,1%) and pharmacists (72,9%) – residents (17,1%) and mentors (20%) - assessed the modified version of the instrument, getting just two highlights (0.2%) related to the clarity of the items, and this version was considered applicable and understandable without the need for additional modifications. Thus, the process of cultural adaptation contributed to the development of a suitable instrument for the Brazilian context, appropriate for use as learning styles identification tool and consequent improvement of pharmacy education in this